Cognitive skills promoted in History and Geography textbooks in Chilean elementary school students. (Innovaciones Educativas, 2022)
The purpose of the study was to analyze the cognitive skills promoted in History and Geography textbooks for seventh and eighth grade and their correspondence with the skills in the Curricular substructure. The research was conducted under the parameters of the integrative method, which uses elements of hermeneutics and descriptive design, using the documentary analysis technique, application of descriptive statistics, quotations, or fragments that allowed data researching and processing. The highest average, present in the school texts, corresponds to the type of creative skills (57.5%), followed by analytical skills (47.0%), and finally, descriptive skills (42.0%) and critical skills (25.0%). It was not possible to observe significant differences between the promotion of cognitive skills according to educational level. In the eighth grade, creative and analytical skills were more frequent than in seventh grade, as was the presence of a greater frequency of critical cognitive skills. It can be concluded that there is a complete correspondence between the cognitive skills of the Curricular substructure and the educational activities proposed in the school textbooks. Likewise, the activities in these texts promote mental operations and procedures, which involve creative, analytical, descriptive, and critical processes. The skills most present in the texts are: observing, explaining, and applying. The most absent skills are: defining concepts, discussing data, promoting imagination, formulating hypotheses, representing chronological sequences, and proposing solutions to problems.
Keywords: cognitive skills; school texts; social sciences; geography teaching; education